PEMBEBASAN BERSYARAT (PB) BAGI PENYALAHGUNA NARKOTIKA DI LEMBAGA PEMASYARAKATAN KLAS I TANJUNG GUSTA MEDAN - Suandi Fernando Pasaribu; Alvi Syahrin; Marlina Marlina; Suhaidi Suhaidi (Universitas Sumatera Utara, 2016)
ABSTRACT One part of coaching Prisoners in the correctional system is the presence of the Parole (Voorwarlijke Invrijheidsteling). Narcotic crime is a crime that is complex because of the narcotic crime, the offender can be at once a victim. Best coaching against inmates is returned / integrated in society and not electrically insulated with iron bars. Based on research conducted by the author in pre Correctional Institution Class I Medan the number of perpetrators of criminal acts resulting in the increasing number of prisoners / prisoners are serving a prison sentence in the Penitentiary. The method used in this research is normative and empirical legal research and analytical descriptive nature by using primary legal materials, secondary and tertiary analyzed normatively. Based on research conducted by the author in pre Correctional Institution Class I Medan the number of perpetrators of criminal acts resulting in the increasing number of prisoners / prisoners are serving a prison sentence in the Penitentiary. Summing up, first, the implementation of parole for abusers of narcotic refers to the Indonesian Government Regulation Number 99 of 2012, Second, efforts to address the employees of prisons are required to discipline the prisoners for good behavior, requiring tightening legislation, increasing the number of prison staff, perform retrieval Quotes Judge (Extra verdict). Third, the supervision of inmates required to report once a month or once every 3 months to Hall of Corrections with program officers visit the client's home to inmates. Keywords: Parole, narcotics abusers, Penitentiary